Agroecological food in local networks in Quito, Ecuador: Cooperativa Sur Siendo Redes y Sabores - Piedra, Andrea Carolina Castillo (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2020)
The study presents the relations of equity between the countryside and the city created by the responsible consumers of Sur Siendo Redes y Sabores cooperative. The cooperative has created market spaces for agroecological products focused on the population of popular social strata that historically lives in a poorly accessible food environment. Through the socio spatial analysis of agro-ecological food in local networks, it was identified that the responsible consumers of this cooperative has created five fairs and a shop. Generating fair trade in the city of Quito with the sale of agroecological products from the rural territories of Pedro Moncayo.